Proficiency Reporting Practices in Research on Second Language Acquisition: Have We Made any Progress?. Issue 1 (26th October 2021) - Park, Hae In; Solon, Megan; Dehghan‐Chaleshtori, Marzieh; Ghanbar, Hessameddin
Abstract: Given that 10 years have passed since the publication of the most recent synthesis of proficiency assessment standards, the present review revisits proficiency assessment practices in research on second language acquisition (SLA), with the goal of examining whether the way in which scholars measure and report proficiency has changed. Our sample included 500 studies from five major SLA‐related journals published between 2012 and 2019. The findings indicate that whereas over 90% of the studies assessed and reported second language proficiency in some way, only 42% of them did so with an independent measure. In line with previous surveys, the most popular assessment technique was institutional status, suggesting that relatively little change has taken place over time. Use or not of an independent measure of proficiency was also found to differ by certain study characteristics (e.g., learner population, research context), providing insight into areas of focus for future improvement. Abstract :